Validation of the AmpFLSTR® NGM select™ PCR amplification kit using ABI PRISM 310® Genetic Analyzer. (December 2015) - Cerri, N.; Cisana, S.; Cortellini, V.; Verzeletti, A.; Agostino, A.; De Ferrari, F.
Abstract: The AmpF l STR ® NGM SElect™ PCR Amplification Kit is a highly robust 17-plex STR genotyping kit developed for human identification laboratories wishing to add the highly polymorphic SE33 locus. In this study, we report the successful analysis of amplicons obtained with AmpF l STR ® NGM SElect™ on the ABI PRISM ® 310 Genetic Analyzer, sequencer still widely used in many forensic laboratories. We performed developmental validation studies following the Scientific Working Group on DNA Analysis Methods (SWGDAM) guidelines, testing several critical areas of kit performance such as sensitivity, DNA mixtures and inhibited samples.